Tujuh Belas Akhlaq Pendidik Dalam Pendidikan Islam - Busthomi, Yazidul (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2022)
The seventeen morals of educators in Islamic education are as follows: 1. Accept questions posed by students and be patient with them. 2. Not in a hurry in all matters. 3. Sit with dignity with calm and bow your head. 4. Do not be arrogant to all humans. 5. Prioritizing tawadu' in meeting places and majlis. 6. Not playing and joking. 7. Show affection to students when teaching. 8. Improve stubborn students with good guidance. 9. Do not scold students who are stubborn and do not insinuate them. 10. Not arrogant, not shy and not ashamed to say: